Um Estudo sobre Espalhamento de Desinformação em Comunidades Antivacina no Telegram - Cavalini, Athus; Comarela, Giovanni (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia); 2025: Anais Estendidos do XXXI Simpósio Brasileiro de Sistemas Multimídia e Web, 2025)
Amid the biggest public health crisis of the century, the COVID-19 pandemic, social platforms amplified the spread of harmful narratives. In this context, this study explores how anti-vaccine communities operated on Telegram. By analyzing nearly 10 million messages from 779 channels and groups, and using machine learning to detect misinformation, harm potential, and toxicity, the results indicate recurring misinformation patterns, high engagement, and links between toxic content and virality. The study provides methodological contributions and insights for understanding and addressing informational disorder on messaging platforms.